2020
DOI: 10.20945/2359-3997000000285
|View full text |Cite
|
Sign up to set email alerts
|

The BRAFV600E mutation analysis and risk stratification in papillary thyroid carcinoma

Abstract: Objective: Although the prognostic role of BRAF V600E mutation in papillary thyroid carcinoma (PTC) is controversial, the American Thyroid Association (ATA) includes the mutational status in their risk stratification system. To evaluate the impact of the BRAF V600E mutation status on PTC risk stratification. Subjects and methods: PTC patients attending a university-based hospital who had the analysis of the BRAF V600E mutation were included. Persistent disease was defined as the presence of biochemical or stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Lower rates of this mutation (45-48%) have been identified in cohorts from South Asia, Central Asia, and the Middle East, whereas the rates in Southeast Asia were 57%. In a study conducted in southern Brazil including patients with PTC, we observed a prevalence of BRAF V600E of 33% [15]. These findings illustrate the heterogeneity of the prevalence of the BRAF V600E mutation in different populations, even in those with comparable genetic backgrounds, and could explain, at least in part, the conflicting results regarding associations between BRAF V600E mutation and outcomes.…”
Section: Prevalence Of Braf Mutations In Papillary Thyroid Cancermentioning
confidence: 50%
See 1 more Smart Citation
“…Lower rates of this mutation (45-48%) have been identified in cohorts from South Asia, Central Asia, and the Middle East, whereas the rates in Southeast Asia were 57%. In a study conducted in southern Brazil including patients with PTC, we observed a prevalence of BRAF V600E of 33% [15]. These findings illustrate the heterogeneity of the prevalence of the BRAF V600E mutation in different populations, even in those with comparable genetic backgrounds, and could explain, at least in part, the conflicting results regarding associations between BRAF V600E mutation and outcomes.…”
Section: Prevalence Of Braf Mutations In Papillary Thyroid Cancermentioning
confidence: 50%
“…We recently evaluated whether the addition of the information about the BRAF V600E mutation status to the risk stratification system proposed by the ATA (2015) would improve the prediction of disease outcome in a cohort of 134 patients with PTC [15]. The information on BRAF V600E mutation status reclassified 12 (8.9%) patients from low to intermediate risk.…”
Section: Association Of Braf Mutations With Clinical and Pathological...mentioning
confidence: 99%
“…• Patients with very low risk of recurrence (< 1%, unifocal, tumor size < 1 cm if PTC), • Patients with PTC with intrathyroidal tumors < 4 cm, without clinical evidence of lymph node metastases or with ≤ 5 microscopic (< 2 mm) lymph node metastases on histology, without vascular invasion, and without an aggressive variant of PTC, and • Patients with well-differentiated follicular thyroid cancer with capsular invasion alone or with less than four foci of vascular invasion. Molecular characterization of the tumor has not been adopted routinely yet, and the impact of BRAF or other (e.g., TERT) mutations on risk assessment is still a matter of debate (13,14).…”
Section: Assessing Disease Persistence/recurrencementioning
confidence: 99%
“…The tall cell variant is the most aggressive tumor, indicating that BRAF mutations are associated with poorer outcomes [9,23]. Other factors associated with the mutation and aggressive tumor phenotype include older age, extrathyroidal tumor invasion, lymph node, and distant metastasis, higher tumor stage, and poorly differentiated cancer [21,22,[24][25][26].…”
Section: Braf Expression In Thyroid Carcinomasmentioning
confidence: 99%
“…A significant improvement has been noted in the knowledge of molecular alterations over the past two decades in all tumors, including thyroid malignancies, and oncogenic BRAF activation represents one of the most prevalent molecular alterations. Reportedly, BRAF mutations are associated with poorer clinicopathological outcomes [ 21 , 22 ]. Among its various subtypes, BRAF most commonly occurred in the tall cell variant of PTC, followed by conventional PTC, and less commonly in the follicular variant of PTC.…”
Section: Introductionmentioning
confidence: 99%